Opportunities And Challenges in the Authorization of the Sanad Talaqqi of The Qur’an in Digital Era (Contrarius Series: Law & Social Justice, 2026)
The rapid advancement of digital technology has reshaped global education and introduced new opportunities and challenges for Qur’anic transmission through ijazah talaqqi with sanad (certified chain of transmission). This study explores the prospects and challenges of authorizing sanad talaqqi in the digital era. A descriptive qualitative approach was employed through library research. Data were collected from journal articles, conference proceedings, books, and working papers. The digital era offers various opportunities, including access to recorded talaqqi sessions, flexible modes of Qur’anic instruction, wider accessibility to sanad talaqqi studies, and the promotion of lifelong Qur’anic learning. However, significant challenges remain, such as issues of teacher integrity and competence, the erosion of traditional etiquettes in Qur’anic transmission, weaknesses in assessment and authorization mechanisms, leniency in conferring sanad, uneven quality among sanad holders, and limitations in technological proficiency. Reforming sanad talaqqi practices in the digital age requires a holistic approach that upholds the principles of talaqqi mushāfahah while safeguarding the ethical and spiritual values of Islamic knowledge transmission. This study contributes to the discourse on modernizing Qur’anic transmission in alignment with the rapidly evolving digital landscape.